The Influence of Tax Planning and EPS on Firm Value in Multinational Companies - Neisya, Audia Ava; Sulastri, Sulastri (JABE (JOURNAL OF ACCOUNTING AND BUSINESS EDUCATION), 2024)
This study aims to examine the influence of tax planning and earnings per share (EPS) on firm value in multinational companies in Indonesia. This study is included in quantitative research which examines data from 43 samples of multinational companies in the consumer cyclicals and consumer non-cyclicals sectors for the period 2020-2022. The findings in this study show that tax planning and EPS have a negative influence on firm value. The findings of this research indicate that companies with low effective tax rate (ETR) values are companies that do a lot of tax planning so that they pay little tax and are considered tax evaders. This can reduce the company's firm value. Apart from that, firm value can experience a decline if the increase in EPS value does not match shareholder expectations. The findings of this study can be used by companies in considering the implementation of tax planning and paying attention to EPS values to increase firm value.